Mineralised wood from Saudi Arabia and Northern Czech Republic - PITERA, Helena; WOJEWODA, Jurand (Geology, Geophysics and Environment, 2010)
In this study two samples of silicified wood were examined. One sample was found on a desert in Saudi Arabia, and the second one was taken in the Czech Republic. The first sample represents the Cretaceous period (Wasia), and the second one - Carboniferous. Both specimens were subjected to the macroscopic inspection, microscopic analysis (in the transmitted light and the scanning microscope). Some point analyses were also carried out, and in the case of the first sample the X-ray analysis was made. In the mineralised wood from Saudi Arabia polluting with organic compounds was detected, as well as presence of calcite and admixtures of clay minerals, and cryptocrystalline pigment of dark brown colour (probably haematite). The sample from the Czech Republic (an outcrop near Trutnov) is strongly silicified. The quartz and chalcedony observed in it are effects of this process. This allows for a conclusion about the presence of two generations of the silica in the sample. The first, earlier generation is represented by quartz; and the later, second generation of silica is the chalcedony. In the case of this sample concentration of fine-grained pigment of brown-red colour is also visible on surfaces of quartz or chalcedony.